(untitled) (Scientific journal of the Fergana State University, 2023)
High-performance liquid chromatography was used to study the flavonoid content of Allium carataviense. As a result of the analysis, hyperazid, rutin, apigenin and gallic acids were found in the ethanol extract of five organs of the plant. Hyperazid, rutin, apigenin and gallic acids in flowers; hyperazid, apigenin and gallic acids were found in the bulb, stem, leaves and seeds. The highest amount of gallic acid was 140,414 mg/100 g in seeds and the lowest amount was 87,145 mg/100 g in stems. The high content of flavonoids was determined in the flowers, which reached 182,113 mg/100 g. The flavonoids robinin, lutein, and quercetin were not detected in flowers, bulbs, branches, leaves, and seeds of Allium carataviense. Hyperazide flavonoid was identified for the first time among the plants of the Allium L. genus in Allium karataviense. The amount of hyperazide in all organs of Allium carataviense was 4,337-10,214 mg/100 g.